Response to Dabrafenib and Trametinib of a Patient with Metaplastic Breast Carcinoma Harboring a BRAF V600E Mutation - Takuji Seo; Emi Noguchi; Masayuki Yoshida; Taisuke Mori; Maki Tanioka; Kazuki Sudo; Akihiko Shimomura; Kan Yonemori; Yasuhiro Fujiwara; Kenji Tamura (Case Reports in Oncological Medicine)
Background. Metaplastic breast carcinomas are rare and carry poor prognoses. They are also more aggressive than other breast cancers and are known for their resistance to chemotherapy. Prolonged treatment with dabrafenib and trametinib is a therapy for malignant melanoma that improves the progression-free survival and overall survival. Such molecular-targeted therapies are also being developed for cancers with BRAF mutation, a driver of malignant melanoma. Case Presentation. A 57-year-old woman with metaplastic breast cancer and chemotherapy-refractory massive pleural effusion. After contained anthracycline regimen failure, her breast cancer progressed to an advanced stage. We ordered next-generation sequencing- (NGS-) based tumor molecular profiling from core needle biopsy of the breast. The NGS report indicated the presence of a BRAF V600E mutation. After initiation of dabrafenib and trametinib, her symptom and the pleural effusion were decreased. The first assessment of CT scans showed a decreased pleural effusion and shrunken subcutaneous lesions. Approximately 2 weeks later, a new lesion appeared. She died from 12 weeks after initiation of dabrafenib and trametinib treatment. Conclusion. To the best of our knowledge, this is the first report of BRAF mutation breast cancer treated with dabrafenib and trametinib and it heralds the possibility of targeted therapy for rare breast cancers.